OWNERSHIP OF LAND RIGHTS BY FOREIGNERS USING THE NAME OF INDONESIAN CITIZENS - Manuaba, Ida Ayu Sintya Naraswari; Setyawati, Dr. Ni Komang Arini; Puspadma, Dr. I Nyoman Alit (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
National land law prohibits land ownership by foreigners, in accordance with Article 9 of the Agrarian Law, which states that only Indonesian citizens can own property rights to land. Meanwhile, Article 26 Paragraph (2) of the Agrarian Law also prohibits the transmission of land ownership rights from Indonesian citizens to foreigners, either directly or indirectly. However, many foreigners control land through certain agreements made before a notary or PPAT. This research is intended to determine and evaluate the validity of land rights acquisition by foreigners and the legal consequences of such acquisition if certain agreements are used. The research method in this research uses a normative legal approach, which focuses on examining legal norms and analyzing library materials to examine the application of positive law. This research indicates that even though formally land ownership by foreigners can be considered legal, it violates Article 26 Paragraph (2) of the Agrarian Law because it is an indirect way to transmit property rights to foreigners. As a legal consequence, land ownership by foreigners through certain agreements is considered null and void, as evidenced in Gianyar District Court Decision Number 259/Pdt.G/2020/PN.Gin because it does not fulfill the objectual requirements under Article 1320 of the Civil Code.